Evaluation of Writing Assignments - Jokić, Anita (European Journal of Multidisciplinary Studies, 2017)
Teaching English as a foreign language is now one of the most important subjects in Croatian secondary schools since English is one of the three obligatory subjects at 'matura' - standardized tests which the seniors need to pass to graduate. Writing is one of the three parts of the EL exam, the other two being listening and reading. When learning a language, students start from listening skill, move on to speaking and reading and finally to most difficult skill to master: writing. Teaching and learning writing faces a lot of challenges since it requires a lot of time to practice and even more to evaluate and monitor progress. Teacher's responsibilities are to regularly provide opportunities to write, encourage students to learn from their mistakes and promote their success. In order to do so, students should be given clear instructions on evaluation/assessment and concise feedback. Since grading written assignments takes up a lot of time, the author proposes rubrics which can be used to assess various types of writing taught at secondary level (description of place/event/person, letters of complaint, job application, invitation, discursive/opinion/for-and-against essay etc.). Author suggests four fixed rubrics and subdivisions: Task completion, Cohesion / coherence, Grammar and Vocabulary. All rubrics and subdivisions are described in the paper. A survey was also conducted on a sample of 140 students and has given an insight into students’ opinion on importance of assessment and feedback and its influence on their progress.
Keywords: English language, evaluation, assessment, writing assignments, rubrics, writing skills